Feeds and Feeding of Ducks in India-An Overview - Naik, Prafulla Kumar; Swain, Bijaya Kumar; Kumar, Dhirendra; Beura, Chandra Kanta (Indian Journal of Animal Nutrition, 2024)
The role of livestock & poultry for nutritional & livelihood security and doubling farmers’ income is highly important. Among alternate poultry species, the contributions of ducks for egg and meat production are next to chicken. In India, the important available ducks are few exotic breeds (Khaki Campbell, White Pekin, etc.) and locally available indigenous breeds (Pati, Maithili, Nageswari, Kuttanad (Chara, Chemballi), indigenous ducks of Tamilnadu (Kollam, Arni, Sanyasi, Keeri), Indigenous ducks (Desi or Kuzi) of Odisha, local ducks of Andaman, etc. Besides, different crossbred and Muscovy (Moti) ducks are also reared in different parts of the country. Generally, the ducks are reared under extensive or semi-intensive or intensive rearing systems. Based on the different rearing systems, the feeds of ducks are more diversified. The literature available on nutrient requirements for different types of ducks and nutrient contents of different feeds in different rearing systems is very meagre. To minimize the cost of production, many locally available low cost feed ingredients or alternate or unconventional feed ingredients like broken rice, azolla, tuber crops (cassava), different insects, earthworm, etc are used for feeding of ducks. Herbal feed additives like ginger and vitamin (Vitamin-C and E) and mineral (Zn and Se) are highly beneficial, when supplemented in duck diets. The feed intake and nutrients metabolisability varies according to the types of ducks, physiological conditions and rearing systems. The important issues with duck feeding are monitoring of feeding, wastage of feed, wetter faeces, Aflatoxins, energy density of the diet, use of fishmeal, fishy flavour of egg, etc. There are many challenges for the optimization of duck production in India. The research carried out on ducks is very limited and more attention should be given on various aspects of duck research. In the promotion of duck farming, the role of Government support through initiations of policies is highly essential. In the scenario of climate change, various nutritional interventions have important role for sustainable duck production, employment generation and in achieving the nutritional & livelihood security of the people of the country.